Penerapan Prinsip Keadilan Dalam Hukum Perdata Di Indonesia - Parlindungan S, Gokma Toni; Suci, Anisa Mutiara; Arisma, Tasya Fazira; Putri, Selvi Kurnia (Journal of Global Legal Review, 2024)
This research aims to analyze the application of the principle of justice in Civil Law in Indonesia, as well as to identify the challenges faced in its practice. This study uses a qualitative method with an empirical approach, which includes a review of laws and regulations, court decisions, and interviews with legal practitioners. The results of the study indicate that although the principle of justice is recognized in Civil Law, its implementation is often hampered by various factors, including the lack of uniformity in legal interpretation and the influence of local culture. This study recommends the need to improve understanding of the principle of justice among law enforcers and the community in order to achieve fairer dispute resolution.